COVID-19 economic impacts in perspective: A comparison to recent U.S. disasters. (15th June 2021) - Rose, Adam
Abstract: This paper places the COVID-19 pandemic into perspective by comparing it to other recent disasters in terms of impacts on the macroeconomy of the U.S. We present a short summary of advances in the state-of-the-art of economic consequence analysis, as well as estimates this approach yields on economic impacts of 9/11, a variety of natural disasters, the Great Recession, and COVID-19. The prevention of these negative impacts represents the benefits of various types of risk management tactics and strategies. In light of the enormously greater economic impact of COVID-19 as compared to natural and man-made disasters, it is reasonable to question whether adequate investments are being made to prevent future pandemics.